PENGARUH WAKTU PROSES DEASETILASI KITIN DARI CANGKANG BEKICOT (Achatina fulica) TERHADAP DERAJAT DEASETILASI - Wahyuni Wahyuni; Ahmad Ridhay; Nurakhirawati Nurakhirawati (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
ABSTRACT Research on the effect of chitin deacetylation processing times from shells of snails on the degree of deacetylation has conducted with a variations of 60 minutes, 90 minutes, 120 minutes and 150 minutes. The purpose of this study was to determine the effect of times improvement in the chitin deacetylation process of the degree of deacetylation. The degree of deacetylation is determined using Fourier Transform Infrared spectroscopy (FTIR). The results show the degree of deacetylation increases with the length of time the process of deacetylation that is 60 minutes to produce the degree of deacetylation of 55.6%, a degree of deacetylation of 90 minutes produces 62.4%, 120 minutes produces 70.3% degree of deacetylation, and time 150 minutes to produce the degree of deacetylation of 84.3%. So that, the length of time spent on the process of deacetylation of chitin from a snail shells, can increase the degree of deacetylation. Keywords: Snail Shells, Times, Degree of Deacetylation, Chitin, Chitosan